Case report: Lichenoid eruption under immunotherapy with MK-4830 and pembrolizumab in a breast cancer patient - Zofia Kachlik; Izabela Błażewicz; Aleksandra Ciarka; Roman J. Nowicki (Frontiers Media S.A., 2024)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, yet they can induce immune-related adverse events (irAEs), including cutaneous toxicities such as lichenoid eruptions. Pembrolizumab, a PD-1 inhibitor, is known for its association with lichen-planus-like reactions, while the side effect profile of combining immunotherapy with MK-4830, a novel fully human IgG4 monoclonal antibody that targets ILT-4, remains limited.Case reportWe present a case of a 47-year-old female with metastatic breast cancer who developed a grade 2 Common Terminology Criteria for Adverse Events (CTCAE) lichenoid reaction after 9 months of MK-4830 and pembrolizumab use. Confluent, erythematous papules with Wickham's striae appeared predominantly on the extremities. Initial therapy with high-potency topical corticosteroids proved insufficient, however prednisone 40 mg daily resulted in satisfactory remission of lichen-planus-like reaction, permitting continued immunotherapy without dosage adjustment.ConclusionThis case highlights the novel occurrence of lichenoid eruption induced by MK-4830 and pembrolizumab in breast cancer treatment. The patient was successfully treated with oral prednisone, which controlled the skin symptoms without interrupting ICI therapy. We emphasize that early diagnosis and treatment of low-grade lichenoid eruption can prevent the cessation of ICIs, thereby combining the benefits of managing irAEs and avoiding cancer progression, leading to a better long-term prognosis.